Exploratory Study on Circular Economy Approaches A Comparative Analysis of Theory and Practice - Frodermann, Laura (Wirtschaftsethik in der globalisierten Welt,, 2018)
The concept of a circular economy gains more and more popularity for companies and politics. In theory the concept holds not only ecological and social but also several economic advantages for the applying companies. This book addresses the following research questions: How is the concept of the circular economy implemented? What impact has the implementation of circular economy on organizations? What are the challenges deriving from circular economy implementation? A qualitative study with companies from various industries in Europe and America has been conducted. Results show that the theoretical comprehensive benefits cannot yet been found in the economy. Finally the central findings are compared to findings in existing literature, contributions to it discussed and a critical view on circular economy provided. Contents Theoretical Foundations.- Research Method.- Case Description and Within-Case Analysis.- Result of Analysis and Interpretations Target Groups Researchers in Business Administration with focus on Sustainable Management, Business Ethics, Innovation Management Manager in the fields of Sustainability, Innovation and CSR The Author Laura Frodermann works as consultant in the corporate development department at a medium-sized company based in Munich.